2012
DOI: 10.2466/24.27.pms.114.2.407-418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baseline Self-Efficacy on Physical Activity and Psychological Stress after a One-Week Pedometer Intervention

Abstract: Physical activity and psychological stress were hypothesized to improve more in participants with high self-efficacy than in those with low and medium self-efficacy, after a one-week intervention. 39 female university students participated. The intervention had two steps: a lecture on self-monitoring and goal setting (160 min.) and a one-week pedometer intervention. Analyses were conducted on tertile groups according to self-efficacy at baseline. Pedometer step counts were higher in the high self-efficacy grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“… 42 People with high and moderate levels of self-efficacy were more predisposed to additional participation in the activities promoting health compared to people estimating their self-efficacy as being low. 43 , 44 In other our study, 45 the mean score of GSES reached 30.98 in residents of PNH and was not significantly lower ( P =0.062), compared to participants of UTA (29.94). The scores obtained in both groups were higher than the overall score (27.32).…”
Section: Discussionmentioning
confidence: 42%
“… 42 People with high and moderate levels of self-efficacy were more predisposed to additional participation in the activities promoting health compared to people estimating their self-efficacy as being low. 43 , 44 In other our study, 45 the mean score of GSES reached 30.98 in residents of PNH and was not significantly lower ( P =0.062), compared to participants of UTA (29.94). The scores obtained in both groups were higher than the overall score (27.32).…”
Section: Discussionmentioning
confidence: 42%
“…It has been known that the effects of exercise reduce stress; however, few studies have reported the accumulation of 10,000 steps a day specifically 22 , 23 . The American College of Sports Medicine (ACSM) and the American Heart Association (AHA) have recommended individual accumulations of at least 30 minutes of moderate-intensity PA (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also observed higher GSES of participants in community development and health promoting activities [ 18 ]. People with high/moderate self-efficacy at baseline were more likely to join additional health promotion activities compared to those with low self-efficacy [ 19 , 20 ], while health promotion intervention could significantly enhance the self-efficacy of participants and vice versa [ 21 , 22 ]. Our study was a cross-sectional analysis, so we cannot determine the causation, but found a positive association between participation and GSES anyway.…”
Section: Discussionmentioning
confidence: 99%